Pengaruh Kompetensi Terhadap Kinerja Karyawan Bagian Produksi Pada Pt. Madeira Indonesia Di Batam - Aripurusa, Andra Farrel; Pangarso, Astadi (eProceedings of Management, 2024)
The purpose of this study is to evaluate and assess how competence affects production workers' performance atBatam's PT. Madeira Indonesia. Up to 45 respondents' data were used in this investigation. This study employed aquantitative research design that made use of parametric inferential statistics and descriptive statistics. In thisinvestigation, non-probability sampling approaches were employed. The statistical package for social science (SPSS)version 25 for Windows was the program utilized in this investigation.The outcome demonstrated that production workers at PT. Madeira Indonesia in Batam perform better and moresignificantly when they are competent. Data analysis revealed that, of the factors examined in this study, othervariables influenced the remaining 66,4% of the relationship between the competency variable (X) and theperformance variable (Y). Keywords-competence, employee performance